2022
DOI: 10.29040/jiei.v8i1.3749
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Intellectual Capital dan Karakteristik Dewan Pengawas Syariah Terhadap Kinerja Sosial Pada Perbankan Syariah

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh intellectual capital, jumlah rapat dewan pengawas syariah, keanggotaan lintas dewan pengawas syariah, dan gender dewan pengawas syariah terhadap kinerja sosial. Populasi yang digunakan dalam penelitian ini adalah Bank Umum Syariah tahun 2008-2020. Teknik pengambilan sampel yang digunakan yaitu teknik purposive sampling sehingga diperoleh sampel sebanyak 131 perusahaan yang telah memenuhi kriteria. Teknik analisis data yang digunakan adalah analisis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Several studies have revealed that the development of Islamic banking performance is in line with the concept of maqashid shariah or social performance such as research conducted by (Mohammed et al, n.d, 2008), (Hammed et al, n.d, 2004), Shaukat (2008), (Apriansyah et al, 2020), (Pratama et al, 2021), (Fatah et al, 2022), The results of the study stated that the practice of measuring performance with the Maqashid shariah approach is a solution to the existing problems regarding performance measurement for Islamic banks.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Several studies have revealed that the development of Islamic banking performance is in line with the concept of maqashid shariah or social performance such as research conducted by (Mohammed et al, n.d, 2008), (Hammed et al, n.d, 2004), Shaukat (2008), (Apriansyah et al, 2020), (Pratama et al, 2021), (Fatah et al, 2022), The results of the study stated that the practice of measuring performance with the Maqashid shariah approach is a solution to the existing problems regarding performance measurement for Islamic banks.…”
Section: Introductionmentioning
confidence: 87%
“…It is explained in the research of (Fatah et al, 2022) that intellectual capital is ownership in the company of various resources such as knowledge, employee expertise, experience, and good relations with parties as part of the value creation process and is considered to be able to achieve competitive advantage in the company. to be able to compete based on the performance of maqashid Syariah in Islamic banking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have explained that a company's competitive advantage can be associated with corporate social performance (Greening & Turban, 2000;Gregory et al, 2016). From an Islamic banking perspective, previous research (Fatah et al, 2022;Nawaz & Haniffa, 2017;Pratama et al, 2020Pratama et al, , 2021Pratama et al, , 2022Setianto & Sukmana, 2016) has shown that IC has a positive impact on Islamic banking performance. Based on the description above, the hypothesis proposed in this study is as follows: H1: Intellectual capital has a positive effect on the Social Performance of Islamic Banks…”
Section: Literature Review and Hypothesis Development The Effect Of I...mentioning
confidence: 98%
“…Islamic banking has the SSB as a part of its structure (Fatah et al, (2022). SSB is tasked with advising the board of directors and monitoring the bank's operations following sharia principles.…”
Section: Introductionmentioning
confidence: 99%